Pharmacophore‐Based Design of Novel Oxadiazoles as Selective Sphingosine‐1‐phosphate (S1P) Receptor Agonists with in vivo Efficacy. Issue 4 (3rd March 2015) - Quattropani, Anna; Sauer, Wolfgang H. B.; Crosignani, Stefano; Dorbais, Jerome; Gerber, Patrick; Gonzalez, Jerome; Marin, Delphine; Muzerelle, Mathilde; Beltran, Fanny; Nichols, Anthony; Georgi, Katrin; Schneider, Manfred; et al.
Abstract: Sphingosine‐1‐phosphate (S1P) receptor agonists have shown promise as therapeutic agents for multiple sclerosis (MS) due to their regulatory roles within the immune, central nervous system, and cardiovascular system. Here, the design and optimization of novel [1, 2, 4]oxadiazole derivatives as selective S1P receptor agonists are described. The structure–activity relationship exploration was carried out on the three dominant segments of the series: modification of the polar head group (P), replacement of the oxadiazole linker (L) with different five‐membered heterocycles, and the use of diverse 2, 2′‐disubstituted biphenyl moieties as the hydrophobic tail (H). All three segments have a significant impact on potency, S1P receptor subtype selectivity, physicochemical properties, and in vitro absorption, distribution, metabolism, excretion and toxicity (ADMET) profile of the compounds. From these optimization studies, a selective S1P1 agonist, N ‐methyl‐ N ‐(4‐5‐[2‐methyl‐2′‐(trifluoromethyl)biphenyl‐4‐yl]‐1, 2, 4‐oxadiazol‐3‐ylbenzyl)glycine (45 ), and a dual S1P1, 5 agonist, N ‐methyl‐ N ‐(3‐5‐[2′‐methyl‐2‐(trifluoromethyl)biphenyl‐4‐yl]‐1, 2, 4‐oxadiazol‐3‐ylbenzyl)glycine (49 ), emerged as frontrunners. These compounds distribute predominantly in lymph nodes and brain over plasma and induce long lasting decreases in lymphocyte count after oral administration. When evaluated head‐to‐head in an experimental autoimmune encephalomyelitis mouse model, together with the marketed drug fingolimod, a pan‐S1P receptor agonist, S1P1, 5 agonist49 demonstrated comparable efficacy while S1P1 ‐selective agonist45 was less potent. Compound49 is not a prodrug, and its improved property profile should translate into a safer treatment of relapsing forms of MS. Abstract : Optimizing for MS: We report a pharmacophore driven optimization of novel oxadiazoles as selective sphingosine‐1‐phosphate (S1P) receptor agonists for the treatment of multiple sclerosis. Compared with the pan‐S1P receptor agonist fingolimod, selective S1P1 agonist45 showed inferior efficacy in an experimental autoimmune encephalomyelitis mouse model, while dual S1P1, 5 agonist49 performed comparably with improved properties.